Unilateral branch retinal artery occlusion due to internal carotid artery occlusive disease in a young adult: a rare case report - Che Mohd Hazidi, Sahel Akmal; Rosli, Abdul Hadi; Abdul Razak, Zulhilmi (2021)
Branch retinal artery occlusion occurs when an artery in the branch retina is blocked, most commonly due to emboli. The sensitive neural tissue of the retina is highly dependent on adequate blood flow and hypoperfusion of retinal tissue can cause visual field loss. We report a case of a 23-year-old librarian presented to us with the complaint of sudden onset painless inferior visual field loss in the right eye for three days. She had no other co-morbidities, was a non-smoker and denied any history of head and neck trauma. Clinical examination revealed vision in the right eye was 6/6 and no Marcus Gunn Pupil with Humphrey Visual Field showed hemifield respecting the vertical meridian at inferior part. IOP was 13 mmHg. Fundoscopy revealed a retinal whitening on the superior part with minimal cotton wool spots and Hollen haurst plaque at end of vessels. Left eye examination was unremarkable, with 6/6 vision. Systemic examination revealed a BP of 121/88 mmHg, no cardiac murmurs and absent carotid bruit. Blood and imaging studies were performed to determine the underlying cause of Branch Retinal Artery Occlusion. These include screening for diabetes, dyslipidemia, valvular or cardiac wall abnormalities, vasculitis, coagulopathies and carotid artery stenosis. The blood investigation results revealed that the patient was dyslipidemic. The Carotid Doppler demonstrated proximal right internal carotid artery thrombosis causing significant Internal Carotid stenosis. An urgent vascular, cardiology & haematology referral was done. Endarterectomy was not required and she was treated conservatively with aspirin and statins.